Adherence level to the World health Organization surgical safety checklist and associated factors in operating rooms in a county teaching and referral hospital in South-Western Kenya - Jonathan Taiswa; Mary Kipmerewo; Alex Chebor; Brian Barasa Masaba (Elsevier, 2023)
Introduction: World Health Organization (WHO) introduced the Surgical Safety Checklist (SSC) in 2008 to assure safety in Operating Rooms (ORs). Globally, adherence level varies with developing countries having the lowest levels compared to their developed counterparts. Objectives: We aimed to assess the level of adherence and identify factors that influence adherence to the WHO SSC in a county teaching and referral hospital in South Western Kenya. Methods: The study preferred a mixed method cross-sectional design. WHO SSC adherence level was assessed by conducting a retrospective review of 424 surgical files that were randomly selected. OR staff (40) were targeted using census method and 31of them were interviewed using structured interviews to determine qualitative data on staff and institutional factors that influenced adherence practices to the WHO SSC. Quantitative data was analysed using Statistical Package for Social Sciences (SPSS). Both descriptive and analytical statistics were generated with statistical significance set at p=<0.05. Content analysis was adopted for qualitative data. Study Findings: WHO SSC was present in 100 % of the post-surgical files. Filling of the WHO SSC was attempted in 7.1 % of the surgeries done. Better adherence was noted in elective surgeries (78 %) compared to emergency (22%) ones. There was a varying adherence level per the type of surgeries with adult general surgeries posting better adherence (40 %) and orthopaedic surgeries were least adherent at 4 %. A decreasing trend in adherence level was noted subsequently through the three moments of surgery ('sign in' (5.7 %); 'Time out' (1.8 %); and 'Sign out' (0.7 %)). The average adherence level was established to be 2.7 %. Key staff factors that influenced adherence practices included; years of experience (p = 0.004), attitude (p = 0.014) and perception(p = 0.009). Additionally, institutional factors were; lack of essential consumables and drugs (77.4 %), lack of refresher trainings (54.5 %), understaffing (48.4 %) and lack of management support (45.2 %). Conclusion: The level of adherence to the WHO SSC was critically low. The aforementioned staff and institutional factors influenced the level of adherence. The study recommends a structured health system-based quality improvement intervention to improve the outcome (adherence) by addressing the root causes (Staff and institutional) to promote patient safety in OR.